Metabolic interpretation of ventilatory parameters during maximal effort test and their applicability to sports - Luis Eduardo Barreto Martins; Lucas Samuel Tessutti; Thiago Fernando Lourenço; René Brenzikofer; Denise Vaz de Macedo (Revista Brasileira de Cineantropometria e Desempenho Humano, 2007)
One important tool for producing specifi c and individualized training intensities is to determine ventilatory threshold (VT), respiratory compensation point (RCP) and maximal oxygen uptake (VO2max) by means of maximum effort testing. However, in order to be able to interpret these data in a wide-ranging manner, it is also important to understand the metabolic responses that occur during the test as the systems transporting and utilizing O2 and producing CO2 adjust. This review article presents an overview of the metabolic responses that take place during a hypothetical maximum effort test, and the applicability of the fi gures thus obtained to the training of athletes. ABSTRACT A determinação das velocidades atingidas no limiar ventilatório (LV), ponto de compensação respiratório (PCR) e consumo máximo de O2 (VO2max) através de um teste de esforço máximo, é uma ferramenta importante para a aplicação de intensidades de treinamento específicas e individualizadas. Mas para poder interpretar os dados de uma forma abrangente, também é importante o entendimento das respostas metabólicas presentes no ajuste dos sistemas de transporte e utilização de O2 e produção de CO2 durante a realização do teste. Esta revisão apresenta um panorama das respostas metabólicas que acontecem durante a realização de um teste de esforço máximo hipotético, e a aplicabilidade dos valores obtidos no treinamento de atletas.